Lire l'Histoire générale des Antilles de J.-B. Du Tertre Exotisme et établissement français aux Îles (1625-1671) - Kullberg, Christina (Brill, 2021)
This book examines the historical ramifications of the concept of exoticism through a literary analysis of Histoire générale des Antilles (1654/1667-71) written by Dominican missionary Jean-Baptiste Du Tertre. The study gives a thorough account of the early French colonization of the islands and the ways in which this violent process of cultural encounters was represented. It argues for the necessity to reconfigure the notion of exoticism, both by revisiting contemporary theorization and by contextualizing it in regard to the history and aesthetics of the times. The study is thus both theoretical, in proceeding by a critical reading of different orientations of exoticism, and historical in offering an in-depth study of an author and a period that have received little attention despite their impact on French Caribbean literature and on the history of anthropology.